A Pelatihan Penggunaan APAR Sebagai Upaya dalam Penanggulangan Bahaya Kebakaran di CV. Soka Mandiri, Sidoarjo: Pelatihan Penggunaan APAR Sebagai Upaya dalam Penanggulangan Bahaya Kebakaran di CV. Soka Mandiri, Sidoarjo - Regina, Amanda; Ratriwardhani, Ratna Ayu; Azzahra Giri, Siti Arrum Julia; Wahyuni, Lilis Hindun; Sunaryo, Merry (LPPI UMN AL WASHLIYAH, 2024)
Occupational Safety and Health is an effort made to ensure the safety and health of workers while in the work environment. Resin is a flammable chemical. From the experience that workers have experienced there, there have been incidents where when workers were mixing these chemicals there were small sparks. The fire triangle is a component of the formation of a fire, as for its components are heat sources, combustible materials, and oxygen. This socialisation is expected for workers to be able to apply APAR in the event of a fire on a small scale for the first handling, not only can apply to the work environment, but also can apply to everyday life. The research method used is to use media questions Pre-test and Post-test. The socialisation that was carried out was successful. This can be concluded from the results of the worker Pre-test of 213.3, then at the time of the Post-test got an increased value of 453.3. This socialisation is very important to be able to do and give to workers, by looking at potential hazards, the work environment, and events that have occurred in this company, namely the occurrence of small sparks. It is hoped that this socialisation can provide additional insight to workers and can apply it as preparedness.